2006
DOI: 10.1002/em.20214
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus induction by metronidazole in rat vaginal mucosa

Abstract: Metronidazole (MTZ) is used for the treatment of many infectious diseases, including vaginal infections. While data indicate that MTZ is mutagenic and induces micronuclei in rodents, there is no information on the genotoxicity of MTZ in epithelial vaginal cells or cervical cells. In the present study, we have instilled MTZ into the vagina of rats and evaluated the micronucleus (MN) frequency in proestrus rat vaginal mucosal cells. The first identified proestrus before treatment was used to establish basal proe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Mutagenic activity, induced by the drug [22] as well as by the urine of therapeutically treated patients [54, 55], was found in bacterial systems. In mammalian cells, some studies [33, 34, 56–65] indicate that MTZ causes a loss of DNA helix content, strand breakage, unscheduled DNA synthesis, and SCEs, whereas others [6672] do not confirm its genotoxicity. In some in vivo studies, MTZ was found genotoxic [73, 74].…”
Section: Introductionmentioning
confidence: 99%
“…Mutagenic activity, induced by the drug [22] as well as by the urine of therapeutically treated patients [54, 55], was found in bacterial systems. In mammalian cells, some studies [33, 34, 56–65] indicate that MTZ causes a loss of DNA helix content, strand breakage, unscheduled DNA synthesis, and SCEs, whereas others [6672] do not confirm its genotoxicity. In some in vivo studies, MTZ was found genotoxic [73, 74].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years MTZ has been re-evaluated regarding its potential cytotoxicity, genotoxicity, reproductive and developmental toxicity in different animal and vegetal in vivo/in vitro model systems [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Ібупрофен неселективно пригнічує циклооксигенезу (СОХ-1 і СОХ-2), що зменшує утворення простагландинів та тромбоксану А2 у місці запалення і тим самим зменшує розвиток запалення, інфільтрацію лейкоцитів, тромбоз судин. Ібупрофен і клотримазол добре переносяться при інтравагінальному введенні, тоді як метронідазол у високих дозах може мати негативні і побічні дії [15]. У зв'язку з цим означена комбінація досліджуваного засобу (ібупрофен, клотримазол, метронідазол) у вигляді супозиторіїв може сприяти зменшенню побічної дії при місцевому застосуванні, крім того, розробка таких засобів у формі вагінальних супозитиріїв дозволяє місцево до-…”
unclassified